Ten-Year Review of Perioperative Complications After Transurethral Resection of Bladder Tumors: Analysis of Monopolar and Plasmakinetic Bipolar Cases - Avallone, Michael A. (J Endourol, 2017)
Objectives: To evaluate the rate of perioperative complications after plasmakinetic bipolar and monopolar transurethral resection of bladder tumor (BTURB and MTURB). In addition, the study identifies patient and procedure characteristics associated with early complications. Patients and Methods: Retrospective review was conducted on patients undergoing transurethral resection of bladder tumor procedures at a single institution from 2003 to 2013 to assess the 30-day complication rates associated with BTURB and MTURB. Results: Four hundred twenty-seven patients met inclusion criteria and underwent 586 procedures (379 BTURB and 207 MTURB). Baseline patient demographics, tumor stage, and tumor grade were similar in BTURB and MTURB cohorts. The overall complication rate was 34.3% for MTURB and 26.7% for BTURB. The most frequent complications were acute urinary retention (AUR) 11%, hematuria 8%, and urinary tract infection (UTI) 7%. There was no statistical difference in rates of AUR, hematuria, UTI, or readmission for continuous bladder irrigation or hemostasis procedures between BTURB and MTURB cohorts. There was a trend toward lower perforation rate during BTURB (2.6% vs 5.8%). In multivariate logistic regression analysis, MTURB, male gender, and large resections were predictive of overall complications. Male gender was associated with hematuria and AUR. Large bladder tumor resection size was also associated with increased risk of overall complications and AUR. Conclusion: BTURB was associated with a lower risk of overall complications, but there was no difference in the rate of hematuria in the two cohorts. Male gender and large tumor size are associated with higher risk of early complications.